Does Earmarking Lead to More per Capita Public Health Spending? - Mukesh Khanal; Jack Mintz; Janice MacKinnon (CESifo GmbH, 2024)
The World Health Organization has advocated the earmarking of health-related taxes to mobilize revenues to be spent on public health spending. While there are certain advantages and disadvantages in the use of earmarked taxes to fund healthcare, its ability to mobilize revenues will depend on whether earmarked taxes are acceptable to voters or not. Earmarking might generate more funding for health care if voters know their tax payments are to be spent on program important to them. However, earmarking might discourage funding if voters are not willing to pay more taxes for health care. Regardless, earmarking will not succeed if government simply replace earmarked taxes for general revenues, leaving public health expenditure untouched. We find that earmarked taxes do not lead to more per capita public health spending in the OECD. If a country has earmarked taxes to support public healthcare, per capita public health spending may decline by over 800, compared to a country with no earmarked taxes supporting public healthcare. The case for earmarking has to be based on other arguments instead.
Keywords: H20; I18; 330; taxation; earmarking; health financing